Destigmatizing Borderline Personality Disorder: A Call to Action for Psychological Science. (March 2023) - Masland, Sara R.; Victor, Sarah E.; Peters, Jessica R.; Fitzpatrick, Skye; Dixon-Gordon, Katherine L.; Bettis, Alexandra H.; Navarre, Kellyann M.; Rizvi, Shireen L.
Despite recognition that borderline personality disorder (BPD) is one of the most stigmatized psychological disorders, destigmatization efforts have thus far focused on the views and actions of clinicians and the general public, neglecting the critical role that psychological science plays in perpetuating or mitigating stigma. This article was catalyzed by recent concerns about how research and editorial processes propagate stigma and thereby fail people with BPD and the scientists who study BPD. We provide a brief overview of the BPD diagnosis and its history. We then review how BPD has been stigmatized in psychological science, the gendered nature of BPD stigma, and the consequences of this stigmatization. Finally, we offer specific recommendations for researchers, reviewers, and editors who wish to use science to advance our understanding of BPD without perpetuating pejorative views of the disorder. These recommendations constitute a call to action to use psychological science in the service of the public good.